A Comparative Perspective on Brain Regeneration in Amphibians and Teleost Fish. Issue 5 (21st February 2019) - Lust, Katharina; Tanaka, Elly M.
Abstract: Regeneration of lost cells in the central nervous system, especially the brain, is present to varying degrees in different species. In mammals, neuronal cell death often leads to glial cell hypertrophy, restricted proliferation, and formation of a gliotic scar, which prevents neuronal regeneration. Conversely, amphibians such as frogs and salamanders and teleost fish possess the astonishing capacity to regenerate lost cells in several regions of their brains. While frogs lose their regenerative abilities after metamorphosis, teleost fish and salamanders are known to possess regenerative competence even throughout adulthood. In the last decades, substantial progress has been made in our understanding of the cellular and molecular mechanisms of brain regeneration in amphibians and fish. But how similar are the means of brain regeneration in these different species? In this review, we provide an overview of common and distinct aspects of brain regeneration in frog, salamander, and teleost fish species: from the origin of regenerated cells to the functional recovery of behaviors.